2020
DOI: 10.1002/ppul.24907
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐related factors associated with pneumonia in 127 children with coronavirus disease 2019 in Wuhan

Abstract: Objective Information regarding the association of immune‐related factors with pneumonia in children with coronavirus disease 2019 (COVID‐19) is scarce. This study aims to summarize the immune‐related factors and their association with pneumonia in children with COVID‐19. Methods Children with COVID‐19 at Wuhan Children's Hospital from 28 January to 12 March 2020 were enrolled. Pneumonia due to causes other than COVID‐19 were excluded. The clinical and laboratory information including routine blood tests, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Of the included reports, 34 (56%) were peer-reviewed journal papers [ 3 , 8 40 ]. Two animal-based, basic science studies were included [ 30 , 41 ] but the overwhelming majority of reports were in humans, for which the most common designs were case-control (n = 26, 43%) [ 10 12 , 14 , 17 , 21 , 23 , 25 29 , 31 , 32 , 37 , 38 , 40 , 42 50 ] and cohort (n = 22, 36%) [ 8 , 13 , 15 , 16 , 20 , 22 , 34 , 36 , 39 , 51 62 ]. 50 studies (82%) considered participants sampled from hospital settings [ 8 , 9 , 11 29 , 31 40 , 42 , 43 , 45 , 46 , 48 50 , 53 , 54 , 56 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the included reports, 34 (56%) were peer-reviewed journal papers [ 3 , 8 40 ]. Two animal-based, basic science studies were included [ 30 , 41 ] but the overwhelming majority of reports were in humans, for which the most common designs were case-control (n = 26, 43%) [ 10 12 , 14 , 17 , 21 , 23 , 25 29 , 31 , 32 , 37 , 38 , 40 , 42 50 ] and cohort (n = 22, 36%) [ 8 , 13 , 15 , 16 , 20 , 22 , 34 , 36 , 39 , 51 62 ]. 50 studies (82%) considered participants sampled from hospital settings [ 8 , 9 , 11 29 , 31 40 , 42 , 43 , 45 , 46 , 48 50 , 53 , 54 , 56 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Children with pneumonia in the setting of COVID-19 have low levels of serum IgA and regulatory (CD4 + CD25 +) T cells, increased levels of high sensitivity (hs)-CRP, IL-10 and procalcitonin [32]. This may, therefore, suggest that dampened serum IgA and decreased circulating regulatory T cells contribute to the deranged immune response against SARS-CoV-2.…”
Section: Clinical Correlation Of Immune Response In Pediatric Covid-19mentioning
confidence: 99%
“…• Two studies found children generally developed a detectable antibody response to SARS-CoV-2 infection [99,100]. • Two studies found children with pneumonia generally mounted lower IgG [101] and IgA responses [102]. • One study found no significant difference between the levels of antibody in children and adults [98].…”
Section: Childrenmentioning
confidence: 99%